Kebijakan Pendidikan Muhammadiyah Terhadap Ordonansi Guru - Setiawan, Farid (Jurnal Pendidikan Islam, 2014)
Muhammadiyah always asserts itself as a social-religious organization to keep it from the (practical) political world. Here, the political potency does not mean that it is in the form of institutional involvement, but it is rather on the policy and the efforts of Muhammadiyah in changing or influencing any policy. The critical attitude of Muhammadiyah organization in moral movement is visible in giving response to policy that is in colonial literature is called the Godsdiensonderwijs. Muhammadiyah attitude toward the teacher ordinance policy is not carried out radically and confrontationally. Muhammadiyah political attitude looks elegant, flexible, and accommodating with a scheme of high politics and allocative politics.